An Update on Advances in COVID-19 Laboratory Diagnosis and Testing Guidelines in India - Kumar, K. S. Rajesh; Mufti, Suhail Sayeed; Sarathy, Vinu; Hazarika, Diganta; Naik, Radheshyam (Frontiers in Public Health, 2021)
The declaration of COVID-19 as a global pandemic has warranted the urgent need for technologies and tools to be deployed for confirming diagnosis of suspected cases. Diagnostic testing for COVID-19 is critical for understanding epidemiology, contract-tracing, case management, and to repress the transmission of the SARS-CoV-2. Currently, routine confirmation of cases of COVID-19 is based on detection of unique sequences of virus RNA by nucleic acid amplification test such as real-time reverse transcription polymerase chain reaction (rRT-PCR). While there are many commercially available RT-PCR assay kits available in the market, selection of highly sensitive and specific validated assays is most crucial for the accurate diagnosis of COVID-19 infection. Laboratory diagnosis plays an important role in disease and outbreak management. Development of rapid point of care tests with better sensitivity and specificity is the critical need of the hour as this will help accurate diagnosis and aid in containing the spread of SARS-CoV-2 infection. Early detection of viral infection greatly enhance implementation of specific public health intervention such as infection control, environmental decontamination and the closure of specific high-risk zones. Creating viral genome repositories and open source databases for use by global researcher is clearly the way forward to manage COVID-19 outbreak and accelerate vaccine development. This review summarizes various molecular diagnostics methods, technical guidelines and advanced testing strategies adopted in India for laboratory diagnosis of COVID-19.